Student Media Sosial Application for Acdemic and Non Acdemic Activities - Weydekamp, Juliando Christian; Purba, Kristo Radion; Liliana, Liliana (Jurnal Infra, 2016)
Social media is an alternative media in the exchange of information both for students of Petra Christian University in improving student learning outcomes. In general, Petra Christian University student using a lentera to get information about the lecture. Lentera so far has not provided facilities that can be used students to get information about the organization and information about the campus. Thus, studentâs use other social media applications, such as BBM, Line, and others as a media of exchanging information alternative about information around the campus.Through this research, made a social media application for students of Petra Christian Universistas that can facilitate students in get and exchange the information such as: lecture information, organizational information, and information about the campus. Making an application equipped with the post, group and chat to facilitate students in exchanging information quickly. Chat features and features created using WebSocket posts created using AJAX.Results obtained from a social media application is made is a student can easily obtain information on campus, such as: information on the lectures, information about the organization and information about the campus. The time it takes students to exchange information by using the chat feature becomes shorter, because it supports real-time communication.Â